Plague, war, and exodus? The effects of desert locust swarms on migration intentions in Yemen - Yashodhan Ghorpade (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2024)
I study the effect of the 2019-21 desert locust outbreak on the intention to migrate among rural households and individuals in Yemen, as an illustration of the human mobility impacts of climate change-related shocks in a complex emergency setting. Using the first systematic household survey conducted in southern Yemen since the beginning of the ongoing conflict, I find that a one standard-deviation increase in exposure to desert locusts increases the individual willingness to migrate (internally or abroad) by 12 percentage points among rural residents. The effects are driven by agriculture-dependent households, plausibly due to the income shock experienced by them as a result of locust exposure. I rule out alternate explanations offered by the selective targeting of aid, selective locust control operations, or the exacerbation of underlying conflict, and argue that the findings are consistent with distress migration. Despite an increase in the willingness to migrate following locust outbreaks, very few people may actually be able to migrate as they lack the necessary resources. As migration intentions may not be realized, most of the affected population may instead be 'trapped'-willing but unable to migrate in response to a formidable natural disaster
Keywords: O12; J61; J68; O15; 330; migration; locust; complex emergency; Yemen; climate change